The impact of excessive protein consumption on human wastewater nitrogen loading of US waters. Issue 8 (21st June 2022) - Almaraz, Maya; Kuempel, Caitlin D; Salter, Andrew M; Halpern, Benjamin S
Abstract : Total and per capita protein consumption rates in US diets, whether from plant or animal sources, rank among the highest in the world. When protein consumption outpaces physiologic protein demands, excess amino acids are degraded in the human body and nitrogen (N) is excreted and released to the environment, mainly in the form of urea. Such excess reactive N can enter downstream environments, thereby impairing human and ecosystem health as well as contributing to economic losses. We show that matching protein consumption with physiologic requirements would reduce US hydrologic N losses to aquatic ecosystems by 12% and overall (atmospheric and hydrologic) N losses to ecosystems by 4%. Were US citizens to consume protein at recommended rates, projected N excretion rates in 2055 would be 27% less than they are today, despite population growth. Optimizing US protein consumption to levels that meet human health standards has environmental benefits on par with improving wastewater treatment using existing technology, while also generating impactful economic benefits.